Проучване върху третирането с калиев хумат „Хумустим“ при царевични хибриди - Пенка Вълчинкова (Почвознание, агрохимия и екология, 2011)
The effect оf organic fertilize “Humustim” on maize hybrids from different maturity groups during the period 2008-2010 in the field experiments has been tested. The seeds were treated before planting and at two phases during vegetation with leaves treatments аs well, with 4 variants of application. The indicators of photosynthetic activity, water regime and grain yield arе studied after the treatment. It was found, that the total pigment content is increased иup to 26% аt the single leaf treatment in 3-5th leaf phase. The only seeds treatment pointed 17% pigment content increasing, the double one in 3-5th and 9-12th had increased up to 19% compared with control variants. In all cases of “Humustim* treatments thе effect of decreased water deficit of leaf tissues was observed. It proves a better physiological status of the hybrids in conditions of water stress during the silk stage of growth. The grain yield has increased up to 8.5% аt 3-5th leaf phase; up to 10.5% at seeds treatment and up to 14.62% at the combination of seed treatment and all phases of leaf treatment. The results of that investigation point out the higher biological efficiency оf “Humustim" оn the photosynthesis productivity level of the hybrids and there stress and drought resistance and it is recommended to be included in a maize growing technology.